DRD2 Agonist Cabergoline Abolished the Escape Mechanism Induced by mTOR Inhibitor Everolimus in Tumoral Pituitary Cells - Mangili, Federica; Esposito, Emanuela; Treppiedi, Donatella; Catalano, Rosa; Marra, Giusy; Di Muro, Genesio; Barbieri, Anna Maria; Locatelli, Marco; Lania, Andrea G.; Mangone, Alessandra; Spada, Anna; Arosio, Maura; et al. (Frontiers in Endocrinology, 2022)
The mammalian target of rapamycin (mTOR) inhibitor everolimus has been shown to display antiproliferative effects on a wide spectrum of tumors. In vitro studies demonstrated that everolimus inhibited pituitary neuroendocrine tumors (PitNETs) cells growth in a subset of patients. Sensitivity to everolimus is reduced by an escape mechanism that increases AKT phosphorylation (p-AKT), leading to pro-survival pathway activation. Dopamine receptor type 2 (DRD2) mediates a reduction of p-AKT in a subgroup of non-functioning PitNETs (NF-PitNETs) and in prolactin-secreting tumor cells MMQ cells, through a β-arrestin 2-dependent mechanism. The aim of this study was to investigate the efficacy of everolimus combined with DRD2 ago-nist cabergoline in reducing NF-PitNETs primary cells and MMQ cells proliferation, to evaluate AKT phosphorylation and a possible role of β-arrestin 2. We found that 9 out of 14 NF-PitNETs were resistant to everolimus, but the combined treat-ment with cabergoline inhibited cell proliferation in 7 out of 9 tumors (-31.4±9.9%, p<0.001 vs basal) reduced cyclin D3 expression. In everolimus unresponsive NF-PitNETs group, everolimus deter-mined a significant increase of p-AKT/total-AKT ratio (2.1-fold, p<0.01, vs basal) that was reverted by cabergoline cotreatment. To investigate the molecular mechanism involved, we used MMQ cells as a model of everoli-mus escape mechanism. Indeed, everolimus did not affect MMQ cells proliferation and increased p-AKT/total-AKT ratio (+1.53±0.24-fold, p<0.001 vs basal), whereas cabergoline significantly reduced cell proliferation (-22.8±6.8%, p<0.001 vs basal) and p-AKT. The combined treatment of everolimus and cabergoline induced a reduction of both cell proliferation (-34.8±18%, p<0.001 vs basal and p<0.05 vs cabergoline alone) and p-AKT/total-AKT ratio (-34.5±14%, p<0.001 vs basal and p<0.05 vs cabergoline alone). To test β-arrestin 2 involvement, silencing experiments were performed in MMQ cells. Our data showed that the lack of β-arrestin 2 prevented everolimus and cabergoline co-treatment inhibitory effects on both p-AKT and cells proliferation. In conclusion, this study revealed that cabergoline might overcome the everolimus escape mechanism in NF-PitNETs and tumoral lactotrophs, by inhibiting upstream AKT activation. The co-administration of cabergoline might improve mTOR inhibitors antitumoral activity, paving the way for a potential combined therapy in β-arrestin 2 expressing NF-PitNETs or other PitNETs resistant to conventional treatments.